PENGGUNAAN BEBERAPA BAHAN ORGANIK TERHADAP VIABILITAS DAN VIGOR BENIH CABAI RAWIT (Capsicum frutescens L.) KEDALUWARSA - Arianto, Aris; Kartika, Kartika; Lestari, Tri (Universitas Lampung, 2025)
One of the techniques that can be applied to overcome seed decline is the invigoration technique using organic materials as priming, namely with young coconut water, bean sprout extract, and aloe vera extract. This study aims to determine the effect of the use of young coconut water, bean sprout extract and aloe vera extract on the viability and vigor of expired cayenne pepper seeds. This study was conducted at the Seed Laboratory of the Agrotechnology Department, Bangka Belitung University. This study used a Completely Randomized Design (CRD) treatment. The treatment given was in the form of organic materials used for priming (Z) with 4 levels of treatment, namely (z0) control, (z1) young coconut water with a concentration of 15%, (z2) bean sprout extract with a concentration of 80%, and (z3) aloe vera extract with a concentration of 50%. Soaking expired cayenne pepper seeds is done for 1 hour. The results of this study indicate that expired cayenne pepper seeds soaked in young coconut water with a concentration of 15% (z1) can increase the parameters of maximum growth potential, seed germination rate, vigor index, plumule length, and dry weight of normal seed sprouts which are better than the control although not significant. The treatment of soaking expired cayenne pepper seeds with organic materials had no significant effect, thought to be due to inaccuracy in the soaking dosage, soaking duration, and abscisic acid content in one of the materials used. Key words: Expired Seeds, Invigoration, Natural Growth Regulator